India-Botswana: Understanding the Partnership of Diamond Sector (IJAS Indian Journal of African Studies, 2023)
The article discusses the evolving relationship between India and Botswana, particularly focusing on trade, investment, and the diamond industry. Botswana, known for its lucrative diamond mines, has seen significant collaboration with India, especially in the small and medium-sized enterprise sector. The diamond industry is a focal point of this partnership. Botswana's diamond mines, particularly the Jwaneng mine, are among the most profitable globally. The article notes that while major diamond companies like De Beers and Alrosa dominate the market, the cutting and polishing of diamonds are often outsourced to Indian firms, particularly in Surat, due to lower labor costs. In this context this article deals with India’s partnership with Africa with special reference to Bostwana. Firstly it taken into account India’s engagement in Diamond Sector. Secondly it explain India’s engagement with Bostwana Diamond Sector. Thirdly it deals with India- Botswana Partnership on Diamond in which the article explore the Political, Cultural and Economic Symmetry and then explain the Policy Calibration in this sector
Keywords: Botswana; Diamond Industry; India; resource development; Strategic Patnership; Value Chain